Re-examination and Re-organization of Relations Between Workers and Management

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryThe Catholic Conference on Social Life was held in Halifax, October 13-15. At this occasion on behalf of Pope John XXIII, Cardinal Cicognani sent the following Message.